Weaving identities : construction of dress and self in a highland Guatemala town - Hendrickson, Carol Elaine, 1949- (University of Texas Press, 1995)
"An innovative ethnography of Maya traje that describes the social life of cloth, its role in the construction of identity, and its part in the changing structure of regional gender relations. Traje empowers, brings women into the global market, and is an enduring of symbol cultural knowledge"--Handbook of Latin American Studies, v. 57.